'A Kind of Homosexual Relation, Disguised': Larkin's Letters to Monica Jones. (15th April 2016) - Underwood, James
Abstract: This essay reads Philip Larkin's letters to his lifelong companion, Monica Jones, in order to present an alternative to the 'easy misogynist' and 'crusty' Tory caricatured and condemned by critics for more than two decades. Exploring Larkin's textual construction of selfhood in these letters, the essay looks at the apolitical nature of the correspondence, its subtly gendered experience of the everyday, and its surprisingly subversive view of sex and sexuality. Anti-essentialist in his approach to gender, Larkin projects a feminine, almost lesbian sensibility. However, by adopting a text-centred approach to the correspondence, this essay also highlights the way in which Larkin's constructed persona obscures and conceals – against the grain of the critical response so far, which has privileged the letters as exceptional in their vulnerability and revealing intimacy.